2009
DOI: 10.1115/1.3066242
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Layer Separation Control With Fluidic Oscillators

Abstract: Fluidic oscillating valves have been used in order to apply unsteady boundary layer injection to “repair” the separated flow of a model diffuser, where the hump pressure gradient represents that of the suction surface of a highly loaded stator vane. The fluidic actuators employed in this study consist of a fluidic oscillator that has no moving parts or temperature limitations and is therefore more attractive for implementation on production turbomachinery. The fluidic oscillators developed in this study genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(23 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…In recent years, these devices have gained renewed interest as flow control actuators. Numerous studies have demonstrated their potential for separation control (e.g., Seele et al 2009;Cerretelli and Kirtley 2009;Phillips and Wygnanski 2013;Woszidlo et al 2014), combustion control (e.g., Guyot et al 2009), and noise control (e.g., Raman and Raghu 2004). Although fluidic oscillators have been successfully employed for flow control, the information available on their fundamental internal and external dynamics remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, these devices have gained renewed interest as flow control actuators. Numerous studies have demonstrated their potential for separation control (e.g., Seele et al 2009;Cerretelli and Kirtley 2009;Phillips and Wygnanski 2013;Woszidlo et al 2014), combustion control (e.g., Guyot et al 2009), and noise control (e.g., Raman and Raghu 2004). Although fluidic oscillators have been successfully employed for flow control, the information available on their fundamental internal and external dynamics remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Although discovered more than fifty years ago at the Harry Diamond Research Laboratories, these devices have mostly been operated with liquids as a working fluid [34,35] (e.g., windshield washers, sprinklers, shower heads, Jacuzzis, etc.). Only in recent years has this concept been applied in conjunction with active flow control (e.g., separation [36,37] , noise [38,39] , and a) b)…”
Section: Introductionmentioning
confidence: 99%
“…Several active and passive concepts to provide the oscillatory character of the emitted jet have been proposed, including selfinduced feedback [43] and external control [42,[44][45][46][47] designs. Early actuators for flow control used a splitter in the outlet nozzle [36,40,55] , which forced the jet to exit through discrete outlets ( Figure 1a) instead of having a continuous sweeping range ( Figure 1b). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…generation of microbubbles [9]) or capability of controlling fluid flows past bodies (e.g. flow separation and transition into turbulence on aeroplane wings [10] or turbine blades [11]). No-moving-part oscillation generators collaborating with pneumatic sensors became also recently popular in no-moving-part fluidic pumps [12,13] handling very dangerous liquids (e.g.…”
Section: Introductionmentioning
confidence: 99%